ANÁLISE DA INFLUÊNCIA DO RESÍDUO DA CONSTRUÇÃO CIVIL NA SUBSTITUIÇÃO PARCIAL DO AGREGADO MIÚDO NATURAL PARA A PRODUÇÃO DE ARGAMASSAS DE CIMENTO PORTLAND - Deschamps, Ryan Stopassoli; Borba, Fernando Gabriel Erbs; Venâncio, Caroline (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
With the civilization advance and the growing demand for solid wastes for the cities development and infrastructure, the reuse of the wastes generated by them can become an environmental and economic alternative. Studies with Civil Construction Waste (CCW) have been increasing and indicating good results partially replaced by the aggregates. It was also noticed that the previous wetting of CCW can show even more promising results. Therefore tests were performed on mortars with 10; 20 and 30% of CCW in a 1: 1: 6 mass scale (cement, lime and aggregate). The same proportions of the respective granulometries were used 1,2; 0.6; 0.3 and 0.15 and the w/c ratio was set at 1.4. After the characterization of the aggregates and agglomerates the mortar was evaluated in the fresh and hard state. The tests were carried out with a specific mass in the fresh and hard state, consistency index, compressive strength at the 7th and 28th days,resistance to bending traction at the 28th, capillary absorption and grip. It has been found that the addition of WCC in mortars can provide improvements when observing that WCC can contribute significantly in the performance of coating mortars when substituted in certain proportions.